Endoscopic R1/Rx Resection of T1 Colorectal Cancer–What Next?. (29th April 2022) - Schmidt, Arthur; Neeff, Hannes Philipp; Quante, Michael
Abstract: T1 carcinoma is often not recognized as such, and inappropriate endoscopic resection techniques are selected, resulting in positive (R1) or nonassessable (Rx) resection margins. Full-thickness resection has been proposed as an alternative to completion surgery. Gijsbers et al. compared oncological outcomes of both strategies. The main finding was that colorectal cancer recurrence was significantly higher in the full-thickness excision of the scar compared with the completion surgery group (9.0% vs 2.2%). However, metastasis-free survival and overall survival were not significantly different in both groups. The results of this study favor full-thickness excision of the scar as the first-line approach for Rx/R1-resected margins but otherwise low-risk tumors.